Regional Regulation No. 1 of 2021 Concerning Implementation of Gender Mainstreaming for the Sleman Regional Government - Sahid Supriyanto; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (PT FORMOSA CENDEKIA GLOBAL, 2022)
Gender is a process for ensuring that women and men have access to and control over resources, obtain development benefits and make the same decisions at all stages of the development process and all government projects, programs and policies (Inpres 9/2000 concerning PUG in National Development). ). Gender equality in development policy is a significant indicator, because gender equality will strengthen a country's ability to develop, reduce poverty and govern effectively. The defense of women's rights began to take effect with the formation of WOMEN in DEVELOPMENT (WID) and is a solution to the problems of Third World women. However, after running for ten years, this program received strong criticism from feminist activists. Because it is considered as a propaganda tool for the First World Agenda to dominate Third World Countries. WID's main agenda is how to involve women in development activities. Because according to him the cause of backwardness of women is because they do not participate in development.